ANALISIS STRUKTUR WACANA NARASI DALAM CERITA BAHASA INGGRIS SISWA SMA SEKOLAH BERSTANDAR INTERNASIONAL DI SEMARANG - Dewi Wahyu Mustikasari; Diana Hardiyanti (Universitas Muhammadiyah Semarang, 2010)
A personal experience story could be joined the narrative, since it has sequence of events. In other word, it has structures. The structures of the personal experience story are Orientation, complication, sequence of events, resolution, and coda. There are two aims in this research. First, to analyze what kinds of narratives’ elements the senior high school students of Sekolah Berstandar International in Semarang apply those. Second, to find out the linguistics features express in each elements of narrative. The researchers used the technique of teknik simak bebas libat cakap. The researhers are not the respondents. There were two steps in gaining the data: the researchers collect the data, then classify it. There were 58 stories. The data was analyzed and clasified based on the elements of narratives: Orientation informs the character, time, place and situation; Complication indicates the point of the story or the development of the conflicts; Sequence of event indicates the climax; Resolution indicates the conclusion or resolution of the conflict; Coda signals the end of the story. The result showed that all the students used Orientation and Complication. On the other hand, sequence of events and resolution were used sometimes. Coda was rarely used by the students. There were four types of typical stories: happy ending, sad ending, bad and surprising experience. The expressions that is being expressed in the linguistic features of the narrative’s elements were the expression of happiness, relieve, worried, and afraid.